A Ptolemaic petition from a ‘Judeo-Egyptian’ (Iudaioaigýptios) - Blumell, Lincoln H. (Journal of Jewish studies, 2024)
This article presents an edition of an unpublished Ptolemaic papyrus presently housed in the Matsushita Museum of Art in Kirishima, Japan. The papyrus comes from a village in the meris of Themistos in the Arsinoite nome (Egypt) and dates to the late third century bce. The most noteworthy aspect of this fragmentary papyrus, which preserves a petition, is that the individual who submitted it bears the compound ethnic identifier ‘Judeo-Egyptian’ (Ἰουδαιοαιγύπτιος), which is hitherto unattested.